2017
DOI: 10.12659/msm.907306
|View full text |Cite
|
Sign up to set email alerts
|

Value of Preoperative Indocyanine Green Clearance Test for Predicting Post-Hepatectomy Liver Failure in Noncirrhotic Patients

Abstract: BackgroundLiver failure is the most feared complication following hepatectomy. Post-hepatectomy liver failure (PHLF) is closely related to the remnant liver volume, and functional reserve. There are several methods for predicting PHLF prior to liver resection. The indocyanine green (ICG) clearance test was popularized in patients with hepatocellular cancer (HCC). We aim to demonstrate the value of preoperative ICG clearance measurement via pulse spectrophotometer (LIMON®) in prediction of PHLF in noncirrhotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As a quantitative test to assess hepatic blood flow and liver function, the ICG clearance test at 15 minutes (ICG-R15) is now commonly used to evaluate reserved liver function in surgical patients. Moreover, ICG-R15 has been proven to be a reliable predictor of PHLF recently (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…As a quantitative test to assess hepatic blood flow and liver function, the ICG clearance test at 15 minutes (ICG-R15) is now commonly used to evaluate reserved liver function in surgical patients. Moreover, ICG-R15 has been proven to be a reliable predictor of PHLF recently (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the efficacy of preoperative ICGR15 for diagnosing ≥ PHLF A was slightly better than that for diagnosing ≥ PHLF B and ≥ PHLF C. However, in general, the diagnostic performance of ICGR15 was not good. This resulted from Cem et al, who demonstrated that the efficacy of the ICG clearance test for PHLF prediction in noncirrhotic patients was unsatisfactory (AUC=0.51, P=0.90) (8). Another study by Wong et al also supported the finding that ICGR15 failed to predict the occurrence of major complications after liver resection (23).…”
Section: Discussionmentioning
confidence: 98%
“…ICG measurement has high buy-in costs for drug and equipment purchases, and its application is not recommended in patients with thyrotoxicosis or iodine allergy, as ICG contains iodine (7). Furthermore, it has been reported that the value of preoperative ICG clearance testing for predicting PHLF in noncirrhotic patients was not satisfactory (8).…”
Section: Introductionmentioning
confidence: 99%
“…Liver resection is an effective surgical treatment for a broad variety of benign and malignant hepatic tumors, post-hepatectomy liver failure (PHLF) remained the most serious complication and the major cause of mortality after liver resections, particularly in patients with suboptimal liver function due to parenchymal liver disease such as cirrhosis or steatosis[15, 16]. Therefore, it is important to estimate liver reserve function before planning partial resection of the liver in order to predict function of the remnant liver[17].…”
Section: Discussionmentioning
confidence: 99%